2011
DOI: 10.1051/0004-6361/201116942
|View full text |Cite
|
Sign up to set email alerts
|

Entropy mode at a magnetic null point as a possible tool for indirect observation of nanoflares in the solar corona

Abstract: Aims. We aim to explore the dynamics of the entropy mode perturbation excited by an energy release in the vicinity of a magnetic null point that is embedded in a gravitationally stratified solar corona. Methods. We solve two-dimensional, time-dependent magnetohydrodynamic equations numerically to find spatial and temporal signatures of the entropy mode that is triggered impulsively by a spatially localized pulse of the gas pressure. Results. We find that the properties of the entropy mode are determined by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…Temperatures with peak at 20,000 K and plasma-β values of maximum 0.557, were found, both within ranges already reported (Ahn et al, 2014;Shimojo et al, 2002), (Antolin & Verwichte, 2011). Regarding our findings on the magneto-acoustic wave, Murawski et al (2011) also found that magnetoacoustic waves were linked to cool dense descending blobs, while Oliver et al (2014) supports that down falling blobs emit small amplitude sound waves of periods of about 100s. It must be stated that our magnetic field strength resembles more that of quiet Sun, rather than an active region case.…”
Section: Discussionsupporting
confidence: 91%
“…Temperatures with peak at 20,000 K and plasma-β values of maximum 0.557, were found, both within ranges already reported (Ahn et al, 2014;Shimojo et al, 2002), (Antolin & Verwichte, 2011). Regarding our findings on the magneto-acoustic wave, Murawski et al (2011) also found that magnetoacoustic waves were linked to cool dense descending blobs, while Oliver et al (2014) supports that down falling blobs emit small amplitude sound waves of periods of about 100s. It must be stated that our magnetic field strength resembles more that of quiet Sun, rather than an active region case.…”
Section: Discussionsupporting
confidence: 91%
“…Ref. 33 and references therein, for the description of the physical properties of the latter, which are out of the scope of this study). Previous theoretical estimations 14,34 show that the characteristic time scale of the thermal conduction is highly sensitive to the equilibrium temperature and density of the plasma and to the wavelength of the oscillation, λ,…”
Section: Dispersion Relation and Characteristic Time Scalesmentioning
confidence: 99%
“…(3) also excites slow and entropy modes (Murawski et al 2011). However, in this study we focus on the time interval associated with the development of fast magnetoacoustic waves.…”
Section: Numerical Modellingmentioning
confidence: 99%